THE CONTEXT OF OCCURRENCE OF ETHICAL DILEMMAS IN THE PROVISION OF SOCIAL HOME SERVICES: EXPERIENCE OF SOCIAL WORKERS - Indrašienė, Valdonė; Katkonienė, Agata; Sadauskas, Justinas (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2017)
The article aims to reveal the context of occurrence of ethical dilemmas providing social in-home services. The paper analyses situations experienced by social workers that determine the occurrence of ethical dilemmas in the provision of in-home services. The study involved 6 social workers providing in-home services with the work experience in service provision from 10 to 14 years. The research data collection method is the semi-structured interview. The data obtained in the interviews were analysed using the descriptive analysis method. Analysing the situation of social in-home services recipients it was observed that social in-home services are provided to the elderly, who, because of illnesses or age, are not able to look after themselves at home, who do not get help from relatives or such help is insufficient. It is stated that not all potential clients accept or get social in-home services. The article distinguishes the following factors influencing the occurrence of ethical dilemmas: conflicts of values, the wish of clients or of their relatives to deny the significance and meaningfulness of the services provided, ill-founded requirements of clients and their relatives, derogation of the professional status of the social worker, the conflict between personal and organizational values and the capability of the social security system.